TARMOQ TEXNOLOGIYALARINI O‘QITISHDAGI ASOSIY MUAMMOLAR HAQIDA - Alaminov, M.X. (SCIENCE and SOCIETY, 2025)
The article examines the problem of teaching network technologies in the context of computer science curricula in the modern education system. Using the works of foreign and domestic scientists as an example are considered various approaches to teaching network technologies. The importance is emphasized of introducing modern network technologies into the educational process.